Influence of elaboration process on chemical, biological, and sensory characteristics of European pennyroyal liqueurs. (9th January 2021) - Rodríguez‐Solana, Raquel; Esteves, Eduardo; Mansinhos, Inês; Gonçalves, Sandra; Pérez‐Santín, Efrén; Galego, Ludovina; Romano, Anabela
Abstract: BACKGROUND: Mentha pulegium is an aromatic and medicinal plant used in different Mediterranean herb‐based liqueurs, whose phytochemical composition depends on the elaboration technique used. The aim of this work was to investigate differences in the sensory, chemical, and biological characteristics of pennyroyal liqueurs elaborated by hydro‐alcoholic (HI) and aqueous (AI) infusions, percolation (P), maceration (M), and distillation (D) techniques, and by the mixture of spirit with pennyroyal essential oil (EO). The volatile composition determined by gas chromatography–mass spectrometry (GC–MS) and gas chromatography coupled to flame ionization detection (GC–FID), the total phenolic (TPC) and flavonoid (TFC) contents, the antioxidant (AC), and enzyme ( α ‐glucosidase, tyrosinase, and acetylcholinesterase) inhibitory capacities, and the sensory analysis by napping, were evaluated in the liqueurs obtained. RESULTS: Monoterpenes and sesquiterpenes were the main volatiles present in liqueurs. The M, P, HI, and AI liqueurs showed the highest TPC, TFC, and AC values; and pulegone, the main hepatotoxic chemotype, was found in concentrations that gave rise to concern. The D and EO liqueurs stand out for their acceptable pulegone content and greater tyrosinase inhibition. Similar liqueur classifications were achieved by sensory analyses, and physico‐chemical and biological analyses using multiple factor and principal component analyses, respectively. CONCLUSION: These results are an important contribution to the identification of the most appropriate elaboration conditions for herbal liqueurs with the healthiest chemical composition and functional properties. © 2020 Society of Chemical Industry